Cloud Multidomain Access Control Model Based on Role and Trust-Degree. (12th April 2016) - Xie, Lixia; Wang, Chong
Abstract : In order to solve the problem of access control among different security domains in cloud networks, this paper presents an access control model based on role and trust-degree. The model combines role-based access control and trust-based access control. The role assessment weights are defined based on the user's role classes, and the trust-degree is calculated according to the role assessment weights and the role's behavior. In order to increase the accuracy of access control, the model gives the concept and calculation methods of feedback trust-degree. To achieve fine-grained access control, the model introduces direct trust-degree, recommendation trust-degree, and feedback trust-degree, all of which participate in comprehensive trust-degree by adjusting their weights. A simulation experiment was conducted in the LAN environment, and a web system was used to construct an access control model with multisecurity domains in the experiment. The experimental results demonstrate that our model has higher security, expansibility, and flexibility.